Motivasi Petani Dalam Membudidayakan Tanaman Nilam (Pogostemo cablin Benth) di Desa Kilambibito Kecamatan Kontukowuna Kabupaten Muna - Halfin, La Ode; Salahuddin, Salahuddin; Wunawarsih, Ima Astuty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2017)
This study aims to determine the motivation of farmers in cultivating patchouli plants. This research was conducted in December 2016 until February 2017. Determination of the sample was done by using Arikunto formula, with a total population of 109 farmers of patchouli, then the number of samples that is as much as 26 people by taking sample as much 25%. The variables observed in this study were 1) the identity of farmers who were included: age, level, normal education, number of family dependents, and land area 2) farmers' motivation in cultivating patchouli plants covering: availability of facilities and infrastructure, the intensity of agricultural extension, And farmer innovation. 3) patchouli cultivation consisting of cultivation of land, nursery, pest control, and patchouli plant disease and harvest and post-harvest. The results showed that the Motivation of patchouli farmers in Kilambibito Village, Kecamatan subdistrict Muna Regency was in the medium category, that is 18 people with the percentage of 70.23%, while the low and high category were each 4 respondents with the percentage of 15.40%.